Case Report: Oculomotor Palsy With Cyclic Spasms in a Patient With Charcot-Marie-Tooth Disease Type 1 - Weber, Konrad P.; Bockisch, Christopher J.; Landau, Klara (Frontiers in Ophthalmology, 2021)
Oculomotor palsy with cyclic spasms is an extremely rare condition whose exact pathophysiology remains a mystery. We followed a boy from the onset of symptoms at the age of ten months until 15 years and documented the case with video oculography. In addition, he was diagnosed with hereditary motor and sensory neuropathy (Charcot-Marie-Tooth disease type 1). Although a pure coincidence cannot be ruled out, it is conceivable that the underlying demyelinating neuropathy of this patient rendered the oculomotor nerve more susceptible to damage.